Association between osteoporosis treatment and severe periodontitis in postmenopausal women. Issue 7 (July 2017) - Passos-Soares, Johelle de S.; Vianna, Maria Isabel P.; Gomes-Filho, Isaac S.; Cruz, Simone S.; Barreto, Maurício L.; Adan, Luis F.; Rösing, Cassiano K.; Trindade, Soraya C.; Cerqueira, Eneida M.M.; Scannapieco, Frank A.
Abstract: Objective: To estimate the association between osteoporosis treatment and severe periodontitis in postmenopausal women. Methods: This cross-sectional study comprised of 492 postmenopausal women, 113 women in osteoporosis treatment, and 379 not treated. Osteoporosis treatment consisted of systemic estrogen alone, or estrogen plus progestin, and calcium and vitamin D supplements, for at least 6 months. Severe periodontitis was defined as at least two interproximal tooth sites with clinical attachment loss of at least 6 mm, and at least one interproximal site with probing depth of at least 5 mm; and dental caries experience was measured using the decayed, missing, and filled teeth (DMFT) index. Analysis included descriptive statistics and Poisson multivariate analysis with robust variance. Results: Women receiving osteoporosis treatment had less periodontal probing depth, less clinical attachment loss, and less gingival bleeding than women not receiving treatment for osteoporosis ( P ⩽ 0.05). In the osteoporosis treatment group, the estimated mean DMFT index score was approximately 20, the most frequent component being the number of missing teeth, and in the nontreated group, the DMFT index was approximately 19. The prevalence of severe periodontitis was 44% lower in the osteoporosis treatment group than in the nontreatment group. The prevalence ratioadjusted was 0.56, 95% confidence interval was 0.31 to 0.99 ( P = 0.05), after adjustments for smoking, age, family income, and visit to the dentist. Conclusions: The results suggest that women treated with estrogen for postmenopausal osteoporosis have a lower prevalence of severe periodontitis than women not receiving treatment. Abstract : Supplemental Digital Content is available in the text